Arab Development Symposium I : Food and Water Security in the Arab World - Rouis, Mustapha; Limam, Imed (World Bank, Washington, DC, 2014)
Recognizing the importance of policy debate and knowledge sharing in the field of development, the Arab Fund for Economic and Social Development and the World Bank (Middle East and North Africa Region) agreed in March 2010 to hold joint high-level development seminars around issues pertaining to the Arab World. These were to be known as the Arab Development Symposia (ADS) and will be held on a regular basis, every 18 months or so, at the Arab Fund premises in Kuwait. The goal was to provide an opportunity for policymakers, practitioners and academicians to share ideas and experiences on topics which are high on the Arab development agenda. As such, the ADS series complement other fora for research and knowledge sharing and dissemination such as the Economic Research Forum (ERF) and the Research Initiative for Arab Development (RIAD).